HIV prevalence and continuum of care among incarcerated people in Iran from 2010 to 2017 - Armita Shahesmaeili; Mohammad Karamouzian; Fatemeh Tavakoli; Mostafa Shokoohi; Ali Mirzazadeh; Samira Hosseini-Hooshyar; Saber Amirzadeh Googhari; Nima Ghalekhani; Razieh Khajehkazemi; Zahra Abdolahinia; Noushin Fahimfar; AliAkbar Haghdoost; et al. (BMC, 2022)
Abstract Background Incarcerated people are at an increased risk of contracting HIV and transmitting it to the community post-release. In Iran, HIV epidemics inside prisons were first detected in the early 1990s. We assessed the HIV prevalence and its correlates, as well as the continuum of care among incarcerated people in Iran from 2010 to 2017. Methods We used data collected in three national bio-behavioral surveillance surveys among incarcerated individuals in 2010 (n = 4,536), 2013 (n = 5,490), and 2017 (n = 5,785) through a multistage cluster sampling approach. HIV was tested by the ELISA method in 2010 and 2013 surveys and rapid tests in 2017. Data on demographic characteristics, risky behaviors, HIV testing, and treatment were collected via face-to-face interviews. HIV prevalence estimates along with 95% confidence intervals (CI) were reported. Using data from the 2017 round, multivariable logistic regression models were built to assess the correlates of HIV sero-positivity and conduct HIV cascade of care analysis. Results The HIV prevalence was 2.1% (95% CI: 1.2%, 3.6%) in 2010, 1.7% (95% CI: 1.3%, 2.1%) in 2013, and 0.8% (95% CI: 0.6%, 1.1%) in 2017 (trend P value < 0.001). Among people with a history of injection drug use, HIV prevalence was 8.1% (95% CI: 4.6%, 13.8%) in 2010, 6.3% (95% CI: 4.8%, 8.3%) in 2013, and 3.9% (95% CI: 2.7%, 5.7%) in 2017. In 2017, 64% (32 out of 50) of incarcerated people living with HIV were aware of their HIV status, of whom 45% (9 out of 20) were on antiretroviral therapy, and of whom 44% (4 out of 9) were virally suppressed (< 1000 copies/ml). Conclusions While HIV prevalence has decreased among incarcerated people in Iran, their engagement in the HIV continuum of care is suboptimal. Further investments in programs to link incarcerated people to HIV care and retain them in treatment are warranted.